The dentin phosphoprotein repeat region and inherited defects of dentin. Issue 1 (7th September 2015) - Yang, Jie; Kawasaki, Kazuhiko; Lee, Moses; Reid, Bryan M.; Nunez, Stephanie M.; Choi, Murim; Seymen, Figen; Koruyucu, Mine; Kasimoglu, Yelda; Estrella‐Yuson, Ninna; Lin, Brent P. J.; Simmer, James P.; et al.
Abstract: Nonsyndromic dentin defects classified as type II dentin dysplasia and types II and III dentinogenesis imperfecta are caused by mutations in DSPP (dentin sialophosphoprotein). Most reported disease‐causing DSPP mutations occur within the repetitive DPP (dentin phosphoprotein) coding sequence. We characterized the DPP sequences of five probands with inherited dentin defects using single molecule real‐time (SMRT) DNA sequencing. Eight of the 10 sequences matched previously reported DPP length haplotypes and two were novel. Alignment with known DPP sequences showed 32 indels arranged in 36 different patterns. Sixteen of the 32 indels were not represented in more than one haplotype. The 25 haplotypes with confirmed indels were aligned to generate a tree that describes how the length variations might have evolved. Some indels were independently generated in multiple lines. A previously reported disease‐causing DSPP mutation in Family 1 was confirmed and its position clarified (c.3135delC; p.Ser1045Argfs*269). A novel frameshift mutation (c.3504_3508dup; p.Asp1170Alafs*146) caused the dentin defects in Family 2. A COL1A2 (c.2027G>A or p.Gly676Asp) missense mutation, discovered by whole‐exome sequencing, caused the dentin defects in Family 3. We conclude that SMRT sequencing characterizes the DPP repeat region without cloning and can improve our understanding of normal and pathological length variations in DSPP alleles. Abstract : We demonstrate that single molecule real‐time DNA sequencing is able to sequence through the lengthy, highly repetitive coding region of dentin sialophosphoprotein (DSPP) and has been used to identify a novel, disease‐causing frameshift mutation in DSPP. A tree generated from the alignment of confirmed dentin phosphoprotein length haplotypes describes how the haplotypes might have evolved.